SPIRIT RINDI - I Kadek Oka Mahendra; I.A.Wimba Ruspawati; A.A.Ayu Mayun Artati (Jurnal IGEL : Journal Of Dance, 2021)
Spirit Rindi dance is a legong dance in the form of a new creation that is danced by six male dancers which inspired from spirit of I Wayan Rindi in legong dance which play a role as figure condong. I Wayan Rindi comes from Banjar Lebah, Sumerta Village, Denpasar City. I Wayan Rindi is a legong dance which acting character legong other that he also as great teacher and educate their students with very good until become a good dancer. The purpose of the Spirit Rindi dance is to introduce the condong dance style I Wayan Rindi's to general public and to preserving classical arts, especially the legong dance.The dance work of Spirit Rindi was created through methode creation from Alma. M. Hawkins with tittle book Creating Through Dance which translated by Y. Sumandiyo Hadi tittled “Mencipta Lewat Tari”. In this methode consists from three step, that this step exploration, step experimental, step forming. Beside use methode also use theory of creation, among other theory aesthetics, theory transformation and than theory motivation. Spirit Rindi dance is divided becomes five structures, that this pepeson, pengawak, pengecet, pengetog, pekaad. Spirit Rindi dance accompanied by gamelan palegongan. The costumes used are red and brown, red which means the power of spirit and brown as a color sweet.Keyword: legong, creation, Spirit Rindi